2018
DOI: 10.1007/s10620-018-4997-4
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship Between Abdominal Symptoms and Fructose Ingestion in Children with Chronic Abdominal Pain

Abstract: BackgroundLimited valid data are available regarding the association of fructose-induced symptoms, fructose malabsorption, and clinical symptoms.AimTo develop a questionnaire for valid symptom assessment before and during a carbohydrate breath test and to correlate symptoms with fructose breath test results in children/adolescents with functional abdominal pain.MethodsA Likert-type questionnaire assessing symptoms considered relevant for hydrogen breath test in children was developed and underwent initial vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(65 citation statements)
references
References 36 publications
5
59
0
1
Order By: Relevance
“…This represented the most frequent abnormality recorded in the medical screening of our study population. This observation is in line with other studies evaluating children with CAP or irritable bowel syndrome (IBS) that reported even higher rates of malabsorption detected by abnormal breath tests (Supplementary Tables S3 and S4) [8,21,[26][27][28][29][30]. Of note, patients in our cohort received diagnostic tests for carbohydrate malabsorption only if they reported abdominal pain associated with dietary intake.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This represented the most frequent abnormality recorded in the medical screening of our study population. This observation is in line with other studies evaluating children with CAP or irritable bowel syndrome (IBS) that reported even higher rates of malabsorption detected by abnormal breath tests (Supplementary Tables S3 and S4) [8,21,[26][27][28][29][30]. Of note, patients in our cohort received diagnostic tests for carbohydrate malabsorption only if they reported abdominal pain associated with dietary intake.…”
Section: Discussionsupporting
confidence: 91%
“…Although carbohydrate malabsorption is frequently detected in children, which corresponds to our findings, symptom relief has not been achieved by elimination of the respective carbohydrate in several randomized controlled trials [29,37]. We report lower dietary response rates to lactose-free or fructose-restricted diet (24% and 18%, respectively) than other studies [8,10,21,28,30,35,38]. However, the best dietary response rates (81-95%) have been reported in patients diagnosed with lactose or fructose intolerance [9,30,38].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations